Evaluation framework for quality management software - Hrgarek, Nadica (Array, 2008)
Summary: Identifying and specifying user requirements is an integral part of information systems design and is critical for the project success. More than 50% of the reasons for the project failure presented in the CHAOS report [36] and study of a US Air Force project by Sheldon et al. [33] are related to requirements. The goal of this paper is to assess the relevant user and software requirements which are the basis for an electronic quality management system selection in medical device companies. This paper describes the structured evaluation and selection process of different quality management software tools that shall support business processes. The purpose of this paper is to help the small to medium size medical device companies to choose the right quality management software which meets the company's business needs